PENERAPAN METODE FULL COSTING PADA PERHITUNGAN HARGA POKOK PRODUKSI SEBAGAI PENENTUAN HARGA JUAL PADA UMKM HOME INDUSTRY TAHU - Vicky Brama Kumbara; Ramdani Bayu Putra; Hasmaynelis Fitri (Jurnal Pengabdian Masyarakat Nusantara, 2022)
One of the small industries in the city of Padang which is engaged in tofu processing is natural tofu SMEs. Natural tofu SMEs are small businesses that are engaged in tofu production and carry out production every day. The tofu processing industry has been established since 1999. The owners of this tofu factory are Mrs. Habiba and Mr. Muakhir who come from the Java area. The tofu production process is carried out right behind Mrs. Habiba's house which is in front of the highway opposite the Lubuk Buaya Padang market. In operating activities carried out by the company, the main product produced is natural tofu, but besides that it is accompanied by various other processed tofu, such as raw tofu which is processed into fried tofu, oncom, beancurd, chips made from soybeans, as well as tempeh and tofu. soy milk. After the implementation of this Community Service activity, it is hoped that the determination of the production price and the determination of the selling price of SME products can be implemented using a new method.